The Influence of Social Media Marketing, e-WOM, Brand Awareness, and Brand Image on Brand Loyalty of Herbs Product - Hendri Dwi Putra; Ditiya Himawati; Dona Suzana; Dina Melia Oktavilantika (Almana : Jurnal Manajemen dan Bisnis, 2023)
One business that is not yet known and has a good effect on health is the herbal extract of gambier, gambir extract herbs can increase health stamina and reduce the effects of smoking on society, this is what makes CV Uncaria Herbal Indonesia (UHI) as a herbal pioneer from gambir extract want to do an analysis that affects brand loyalty in each of its products. This research aims to determine and analyze the influence of social media marketing, e-WOM, brand awareness, and brand image on brand loyalty at Uncaria Herbal Indonesia. The method of this research in this research was a questionnaire filled out by respondents, namely CV UHI customers who are active on social media. A sampling of 150 respondents in this study using the Accidental Sampling method. This study uses descriptive analysis. Based on the results of research using SPSS. Through the results of this research, it can be concluded that there is a positive and significant influence of social media marketing, e-WOM, Brand awareness, and brand image on Brand loyalty.